Team roles at work - Belbin, R. M. (Butterworth-Heinemann, 2010)
Team Role theory is a familiar concept for managers and management trainers. This book provides useful insights into how to apply the theory in everyday work situations. It explores the impact of Team Roles from interpersonal chemistry and managing difficult relationships, to cultivating effective leaders and shaping organizations.